2009
DOI: 10.1109/jlt.2008.2011820
|View full text |Cite
|
Sign up to set email alerts
|

Stability Comparison of Two Ring Resonator Structures for Multiwavelength Fiber Lasers Using Highly Doped Er-Fibers

Abstract: An experimental comparison of stability between two different fiber laser topologies is carried out. The lasers are based on ring resonators that include highly-doped Er-fibers. Both topologies use fiber Bragg grating reflectors in order to select the emission wavelengths. The experimental results confirms that the novel topology based on fiber optic circulators arranged in an hybrid serial-parallel configuration offers a better stability and higher optical signal to noise ratios (OSNR) than the simpler based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 13 publications
2
26
0
1
Order By: Relevance
“…However, some alternative fiber laser configurations have been shown, where these kinds of devices can be suppressed from the cavity rings by using optical circulators [7]. Theoretically, a polarization controller is also needed for conventional doped fiber that does not preserve polarization.…”
Section: Fiber Lasers Designmentioning
confidence: 99%
See 3 more Smart Citations
“…However, some alternative fiber laser configurations have been shown, where these kinds of devices can be suppressed from the cavity rings by using optical circulators [7]. Theoretically, a polarization controller is also needed for conventional doped fiber that does not preserve polarization.…”
Section: Fiber Lasers Designmentioning
confidence: 99%
“…Theoretically, a polarization controller is also needed for conventional doped fiber that does not preserve polarization. However, some works [7] have demonstrated that this device has little influence on the multiwavelength regime. Ring fiber lasers are also known to be susceptible to power fluctuations.…”
Section: Fiber Lasers Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of this, different doped fiber lengths were studied in order to maximize the output power for each value of launched pump power. However, the stability dependence is non-monotonic and strongly depends on the active fiber length [12][13][14].…”
Section: Resultsmentioning
confidence: 99%